SEJARAH SINGKAT PENDIDIKAN ISLAM (TINJAUAN KRITIS) - Fahmiyudin, Muhamad; Dhohiri, Daud; Mutaqin, Mumu Zainal; Arifin, Muhammad (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
ABSTRACT Islamic education has played a pivotal role in shaping the character, morality, and intellectual development of Muslim communities since the 7th century CE. This study examines the historical evolution of Islamic education, focusing on the role of madrasahs as formal educational institutions, and analyzes the challenges and opportunities presented by globalization and digital transformation. This study uses a qualitative approach based on a literature review to analyze various dimensions of Islamic education, from the history of its development to the challenges faced in the modern era. Employing a critical literature review methodology, the research encompasses a historical analysis of Islamic education's development and foundational principles, a critical evaluation of madrasahs' role in providing holistic education, and a contemporary analysis of the challenges and opportunities arising from globalization and digital innovation. Findings indicate the necessity for curriculum reform that integrates Islamic values with 21st-century competencies, enhancement of educators' digital proficiency, and optimal utilization of technology to ensure the continued relevance of Islamic education amidst dynamic social changes. In conclusion, Islamic education must preserve its core values while adapting to contemporary demands to cultivate generations endowed with moral integrity and modern competencies. ABSTRAK Pendidikan Islam telah memainkan peran sentral dalam membentuk karakter, moral, dan intelektual komunitas Muslim sejak abad ke-7 M. Penelitian ini mengkaji evolusi historis pendidikan Islam, dengan fokus pada peran madrasah sebagai lembaga pendidikan formal, serta tantangan dan peluang yang dihadapi dalam era globalisasi dan transformasi digital. Penelitian ini menggunakan pendekatan kualitatif berbasis tinjauan literatur untuk menganalisis berbagai dimensi pendidikan Islam, mulai dari sejarah perkembangannya hingga tantangan yang dihadapi di era modern. Melalui tinjauan literatur kritis, analisis dilakukan terhadap perkembangan pendidikan Islam dan prinsip-prinsip dasarnya, evaluasi peran madrasah dalam menyediakan pendidikan holistik, dan identifikasi tantangan serta peluang yang muncul akibat globalisasi dan inovasi digital. Hasil penelitian menunjukkan perlunya reformasi kurikulum yang mengintegrasikan nilai-nilai keislaman dengan kompetensi abad ke-21, peningkatan kompetensi digital pendidik, dan pemanfaatan teknologi secara optimal untuk memastikan relevansi pendidikan Islam di tengah perubahan sosial yang dinamis. Kesimpulannya, pendidikan Islam harus mempertahankan nilai-nilai inti sambil beradaptasi dengan tuntutan kontemporer guna mencetak generasi yang memiliki integritas moral dan kompetensi modern.